Elastomeric polymers with high rate sensitivity : applications in blast, shockwave, and penetration mechanics - Barsoum, R. G. S. (PDL handbook series., 2015)
Recent investigations into blast-resistant properties of polyureas and other multi-phase polymeric elastomers indicate that they can dissipate broad bands of frequencies such as those encountered in blast events. In this unique book, Elastomeric Polymers with High Rate Sensitivity, Dr. Roshdy Barsoum and expert contributors bring together the cutting-edge testing methodologies, material properties, and critical design data for engineers seeking to deploy this technology. Where conventional methods of resisting blast, shockwave, and penetration are expensive, time-consuming and impractical,